Gambaran Kualitas Tidur Lansia Di Satuan Pelayanan Rehabilitasi Sosial Lanjut Usia Kabupaten Garut - Jemi, Jemi Rahmani A; Setiawan, Setiawan; Udin, Udin Rosidin (JURNAL KESEHATAN KARTIKA, 2019)
Elderlies experience various changes, both in physical and psychological aspect.Degenerative diseases is also experienced by the elderlies. This situation is a high risk andcan caused poor sleep quality due to various factors. Elderlies in the elderly socialrehabilitation service units are less productive during the day and sometimes do notparticipate in existing programs or activities.The purpose of this research was to find out thedescription of sleep quality in elderlies in the Elderly Social Rehabilitation Services Unit ofGarut Regency. Population in this research was 75 people, and 53 people became sampletaken by consecutive sampling technique. The Pittburgh Sleep Quality Index (PSQI)instrument was used to measure sleep quality. Data analysis used univariate to determine thefrequency distribution of quality sleep of the elderlies. The study was conducted from April toJune 2019.The results of this study found that the elderly sleep quality category in the ElderlySocial Rehabilitation Service Unit of Garut Regency was dominant in the bad category(64.2%). Other results were components of sleep disorders (96.2%), sleep duration (30.2%),and activity dysfunction during the day (32.1%) were the causes of poor quality sleep in theelderly. Nurses and nursing homes are expected to know the quality of sleep in the elderly tobe able to provide appropriate interventions for elderly who experience sleep disorders bymaintaining an adequate sleeping environment so that the elderly can meet their sleep needs